MCRT, a multifunctional ligand of opioid and neuropeptide FF receptors, attenuates neuropathic pain in spared nerve injury model. Issue 6 (15th February 2021) - He, Chunbo; Wang, Xiaoli; Zhang, Jing; Wang, Hao; Zhao, Yaofeng; Shah, Jagat Narayan; Ma, Chan; Li, Hailan; Su, Wenting; Zhang, Zhe; Chen, Shasha; Zhou, Lanxia; et al.
Abstract: Chimeric peptide MCRT (YPFPFRTic‐NH2 ) was a multifunctional ligand of opioid and neuropeptide FF (NPFF) receptors and reported to be potentially antalgic in acute tail‐flick test. Here, we developed spared nerve injury (SNI) model to explore its efficacy in chronic neuropathic pain. Analgesic tolerance, opioid‐induced hyperalgesia and gastrointestinal transit were measured for safety evaluation. Intracerebroventricular (i.c.v.) and intraplantar (i.pl.) injections were conducted as central and peripheral routes, respectively. Results demonstrated that MCRT alleviated neuropathic pain effectively and efficiently, with the ED50 values of 4.93 nmol/kg at the central level and 3.11 nmol/kg at the peripheral level. The antagonist blocking study verified the involvement of mu‐, delta‐opioid and NPFF receptors in MCRT produced anti‐allodynia. Moreover, the separation of analgesia from unwanted effects was preliminarily achieved and that MCRT caused neither analgesic tolerance nor hyperalgesia after chronic i.c.v. administration, nor constipation after i.pl. administration. Notably, the local efficacy of MCRT in SNI mice was about one thousandfold higher than morphine and ten thousandfold higher than pregabalin, indicating a great promise in the future treatment of neuropathic pain.